PENGARUH KEPEMIMPINAN YANG MELAYANI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA DENGAN BUDAYA ORGANISASI SEBAGAI MODERASI (Studi Pada Sekretariat Daerah Kabupaten Pati) - Dwijayanto, Faizal; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2019)
This study aims to determine the effect of servant leadership and Quality of Work Life on the performance by organizational culture as a moderating variable in the Sekretariat Daerah Pati Regency. Analysis tool used is multiple regression, as for testing the hypothesis using a t test. Data collection through questionnaires to measure using Likert scale of 7 (seven) alternative answers. Object of research is employees at Sekretariat Daerah in Pati regency. Number of samples in this study were 111 respondents. Sampling technique using the purposive sampling. Survey results revealed that servant leadership has positive effects on performance in the Sekretariat Daerah Pati Regency. Quality of Work Life has positive effect on the performance in the Sekretariat Daerah Pati Regency. Organizational culture has positif effect on performance in the Sekretariat Daerah Pati Regency. Organizational culture does not moderate the effect of servant leadership on performance in the Sekretariat Daerah Pati Regency. Organizational culture does not moderate the effect of Quality of Work Life on performance in the Sekretariat Daerah Pati Regency. Key words : Servant leadership, Quality of Work Life, Organizational culture and Performance